2009
DOI: 10.1177/156482650903000204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Positive Deviance Approach to Improve the Effectiveness of an Iron-Supplementation Program to Control Nutritional Anemia among Rural Senegalese Pregnant Women

Abstract: (adjusted odds ratio, 0.25; 95% confidence interval, 0.12 to 0.53).Conclusions. This intervention shows that a community-based strategy, such as the positive deviance approach, can contribute to improving the effectiveness of iron supplementation during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 24 publications
2
36
0
2
Order By: Relevance
“…Ndiaye et al (32) 2009 Senegal Monthly health promotion sessions for pregnant women through community volunteers…”
Section: Strengths Of Community-based Distribution Of Ironfolic Acid mentioning
confidence: 99%
See 2 more Smart Citations
“…Ndiaye et al (32) 2009 Senegal Monthly health promotion sessions for pregnant women through community volunteers…”
Section: Strengths Of Community-based Distribution Of Ironfolic Acid mentioning
confidence: 99%
“…Six studies found that CBD of IFA supplementation can increase ANC attendance through community agents encouraging earlier and consistent ANC visits (25,26,28,(30)(31)(32) . In Nepal, a programme with community volunteers that distributed IFA supplements found a substantial increase in compliance (defined as those taking 80 % of the recommended number of supplements) and increased ANC attendance through community volunteers, which dispelled a common local belief that community distribution would discourage women from seeking care at health facilities (33) .…”
Section: Strengths Of Community-based Distribution Of Ironfolic Acid mentioning
confidence: 99%
See 1 more Smart Citation
“…This theory posits that there are some individuals who may thrive despite an adverse environment and without extra resources. This approach has been tested and has proven successful in addressing malnutrition, 9 iron deficiency anemia, 10 and recently adult obesity. 11 The benefit of a positive deviance strategy is that it utilizes local resources and people, deriving solutions from the community, thus enhancing both acceptability and sustainability in the community.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Ndiaye M. et al which compared positive deviance approach with an ongoing integrated nutrition and health program intervention (Micah) in a rural Senegalese area found that a community-based strategy, such as the positive deviance approach, could contribute to improving the effectiveness of iron supplementation during pregnancy. 29 In India, some interventions used the "positive deviance approach" (e.g., the Adolescent Anemia Control Program for Girls in Vadodara District and the UMANG Project in Uttar Pradesh) with significant results and this approach should be further implemented and documented.…”
Section: Using Positive Deviance Approach As a Toolmentioning
confidence: 99%